2004
DOI: 10.1111/j.1083-4389.2004.00240.x
|View full text |Cite
|
Sign up to set email alerts
|

Total Family Unit Helicobacter pylori Eradication and Pediatric Re‐Infection Rates

Abstract: This study is the first to evaluate the effect of total family unit H. pylori eradication on pediatric re-infection rates and reports the longest period of re-infection follow-up in children. In childhood, re-infection with H. pylori is not significantly reduced by family unit H. pylori eradication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 19 publications
1
24
0
2
Order By: Relevance
“…The index children were followed up with UBT. One of 26 children was infected in the former group, and three of 24 in the latter group ( p = .34) [13]. In Gambia, 12 village clusters were randomly allocated to insecticide and control groups and the frequency of infectious diseases was compared.…”
Section: Prevalence Transmission and Risk Factors Of Helicobacter Pmentioning
confidence: 99%
“…The index children were followed up with UBT. One of 26 children was infected in the former group, and three of 24 in the latter group ( p = .34) [13]. In Gambia, 12 village clusters were randomly allocated to insecticide and control groups and the frequency of infectious diseases was compared.…”
Section: Prevalence Transmission and Risk Factors Of Helicobacter Pmentioning
confidence: 99%
“…Additional drugs include rifampicin and its more effective analog, rifabutin, which both have excellent in vitro activity against H. pylori and have been used in second‐ and third‐line therapy approaches . Once successfully eradicated, the reinfection rate is low in Western European children and not significantly further reduced by additional treatment of other family members …”
mentioning
confidence: 99%
“…Our study of 136 children revealed a high recurrence rate of 25.2% during the first year after successful eradication of H. pylori infection. In developed countries, reported recurrence rates in children have varied between 2.3 and 12.8% . Almost no studies have investigated H. pylori recurrence rates in children in developing countries.…”
Section: Discussionmentioning
confidence: 99%